Use of QuantiFERON-TB Gold In-tube assay in screening for neutralizing anti-interferon-γ autoantibodies in patients with disseminated nontuberculous mycobacterial infection. (February 2018) - Wu, U.-I.; Chuang, Y.-C.; Sheng, W.-H.; Sun, H.-Y.; Jhong, Y.-T.; Wang, J.-Y.; Chang, S.-C.; Wang, J.-T.; Chen, Y.-C.
Abstract: Objective: Anti-interferon- γ (IFN-γ) autoantibodies (anti-IFN-γ Abs) have been increasingly recognized as an important cause of disseminated nontuberculous mycobacterial (DNTM) infection, and identification of this immunodeficiency impacts clinical management. However, the protean disease manifestations and inaccessibility to diagnostic tests in clinical settings hamper its early diagnosis. Here, we sought to determine whether QuantiFERON-TB Gold In-tube (QFT-GIT), a commercialized IFN-γ release assay, could be used to screen for neutralizing anti-IFN-γ Abs among previously healthy adults with DNTM infection. Methods: Non-HIV patients with DNTM infection were prospectively enrolled for the QFT-GIT assays. We measured their plasma concentration of anti-IFN-γ Abs and their neutralizing capacity through enzyme-linked immunosorbent assay and flow cytometry. We then analysed the correlation between QFT-GIT results and the presence of neutralizing anti-IFN-γ Abs among patients with and without previously recognized immunosuppression, respectively. Results: Irrespective of the autoantibody concentration or disease activity, all patients with neutralizing anti-IFN-γ Abs (100%, 30/30) had indeterminate QFT-GIT results because of extremely low or undetectable IFN-γ levels in the mitogen tubes. None of the four DNTM patients who were previously healthy and tested negative of anti-IFN-γ Abs had an indeterminate QFT-GIT result, and their IFN-γ levels in the mitogen tube were significantly higher than those of the patients with anti-IFN-γ Abs (8.28 IU/mL vs. 0.05 IU/mL, p 0.001). Conclusion: An indeterminate QFT-GIT result because of undetectable or extremely low IFN-γ level in the mitogen tube suggests the presence of neutralizing anti-IFN-γ Abs in a previously healthy patient with DNTM infection.